Characterization and manufacturing conditions of cooked local chicken sausage in Benin - GBAGUIDI, Mauricette; KPATINVOH, Brice T. Dieu-Grand; Aboudou, Kowiou; DEGNON, Gnimabou René (My University, 2023)
Sausages are among the most common processed meat products in the world. The optimization of the manufacturing conditions makes it possible to reduce and determine the optimal conditions for manufacturing the sausage. For this fact, a material balance, a determination of the nutritional, physicochemical and sensory characteristics and the relationship that binds these different parameters have been. Two manufacturing technological diagrams have been adopted, namely the technological diagram for manufacturing local cooked chicken sausage with cooking in water (T5 1) and steam cooking (T5-2). The results showed that approximately 25% of losses are recorded grouping the bones and the aponeuroses in the two cases of technologies. At the end of the embossing, about 3.5% loss stuck in the machines and no significant difference (p˃0.05) is observed at the level of the two cooking methods. After cooking, part of the sausage is deformed due to the increase in temperature. This loss is more remarkable (7.83%) for steam cooking (T5 2). At the end of the process, the yield is 94.46% for the T5-1 technology and 88.40% for the T5-2 technology. As for the nutritional and physicochemical results of local chicken sausages, they vary from one technology (T5-1) to another (T5-2)
Keywords: Sausages; Characteristics; Nutritional; Physicochemical; Sensory